Ex Vivo Pharmacokinetics and Pharmacodynamics Modeling and Optimal Regimens Evaluation of Cefquinome Against Bovine Mastitis Caused by Staphylococcus aureus - Jiang, Li-jie; Xiao, Xia; Yan, Ke-xu; Deng, Tian; Wang, Zhi-qiang (Frontiers in Veterinary Science, 2022)
Cefquinome, the fourth-generation cephalosporin applied solely for veterinary medicine, was commonly used for bovine mastitis caused by S. aureus. The present study aims to establish an optimal dose and provide a PK/PD Cutoff value (COPD) for cefquinome against Staphylococcus aureus based on ex vivo pharmacokinetics and pharmacodynamics (PK/PD) integration. In this study, it was carried out to investigate the pharmacokinetic (PK) of cefquinome when administrated three consecutive intramammary (IMM) cefquinome in three healthy dairy cows at 75 mg/gland, drug concentration was determined by HPLC-MS/MS assay. Ex vivo pharmacodynamics (PD) of cefquinome was evaluated by using milk sample from PK experiment. The relationship between the AUC/ MIC of cefquinome and bacterial loading reduction was simulated using a Sigmoid Emax model. The cefquinome concentration in milk attained a maximum level of 1.55±0.21 mg/mL at 1.8 h after the third administration. The mean value of the area under the concentration-time curve (AUC0-24) was 26.12±2.42 mg•h/mL after the third administration. The elimination half-life was 10.6 h. For PD profile, the MICs of cefquinome in milk were 2-4 times higher than those in the broth. In vitro time-killing curve shown that initial bacterial concentration poses a huge impact on antibacterial effect on three strains. The antibacterial effect was weakened with the initial bacterial concentration increasing from 106 to 108 CFU/mL. The AUC0-24h/MIC index correlated well with ex vivo efficacy both for the initial inoculum of 106 CFU/mL and 108 CFU/mL (R2> 0.84). According to the inhibitory sigmoid Emax model analysis, the PK/PD surrogates (AUC0-24/MIC) values were 8638, 1397, and 3851 for bactericidal effect (E = −3) with an initial inoculum of 106 CFU/mL, while the corresponding values were 12266, 2295 and 5337 respectively with the initial inoculum of 108 CFU/mL. The ex vivo PK/PD based population dose prediction indicated a target attainment rate (TAR) of 90% of 55 mg/gland/12 h. The COPD for cefquinome against S. aureus was 2 μg/mL under the recommended dose of 55 mg/gland/12 h. However, it should be validated in clinical practice in future investigations. These results contributed to the rational usage of cefquinome for mastitis treatment in clinical veterinary medicine.